2010
DOI: 10.1111/j.1365-2567.2010.03269.x
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin induces Foxp3+ T regulatory cells by modulation of transforming growth factor‐β signal transduction

Abstract: SummaryStatins are widely used drugs for the treatment of hypercholesterolaemia. A number of recent studies have suggested that statins also have pleiotropic effects on immune responses and statins have proven to be effective in the treatment of autoimmune diseases in animal models. Foxp3 + T regulatory cells are a unique subset of CD4 + T cells that mediate immunosuppression. Foxp3 + T cells develop in the thymus, but can also be induced in peripheral sites in the presence of transforming growth factorb (TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 23 publications
(62 reference statements)
5
76
0
4
Order By: Relevance
“…57; www.clinicaltrials.gov: NCT02596893). In addition, simvastatin efficiently abrogates Smad7, resulting in a higher frequency of FoxP3 + Tregs in mice (58). Notably, none of these drugs were cell type-specific.…”
Section: Cd103mentioning
confidence: 99%
“…57; www.clinicaltrials.gov: NCT02596893). In addition, simvastatin efficiently abrogates Smad7, resulting in a higher frequency of FoxP3 + Tregs in mice (58). Notably, none of these drugs were cell type-specific.…”
Section: Cd103mentioning
confidence: 99%
“…Given the potential effects of statins independent of their lipid lowering abilities, statins are great candidates for repurposing. Studies to explore these non-cholesterol associated effects have shown that statins inhibit cytokine-inducible expression of the co-stimulatory molecules necessary for T-cell activation, increase the number and suppressive function of regulatory T-cells and reduce disruption of the endothelial cell junction [7][8][9]. Statins have also been shown to reduce epithelial to mesenchymal transition, to inhibit the secretion of matrix metalloproteinases (MMPs) by myofibroblasts, and to increase the number of circulating endothelial progenitor cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…These data suggest that rosuvastatin inhibitory effects on TSC2 -/meth ASM cell proliferation might be dependent on its demethylating properties on TSC2 gene that promote the expression of tuberin, thus normalizing the rate of cell proliferation. Several evidences show that statins may act as epigenetic modulators in different cell types (Kim et al, 2010;Kodach et al, 2011). The effects of simvastatin on immunosuppression are associated with demethylation of the Foxp3 promoter, because it exerts a potent synergistic effect on Foxp3 induction when combined with a low concentration of TGF-b in T cells (Kim et al, 2010).…”
Section: Fig 2 Evaluation Of Pi3k and Mapk Pathways In Tsc2mentioning
confidence: 99%
“…Several evidences show that statins may act as epigenetic modulators in different cell types (Kim et al, 2010;Kodach et al, 2011). The effects of simvastatin on immunosuppression are associated with demethylation of the Foxp3 promoter, because it exerts a potent synergistic effect on Foxp3 induction when combined with a low concentration of TGF-b in T cells (Kim et al, 2010). Lovastatin inhibits the DNA methyltransferase activity and promotes the demethylation of the promoters of bone morphogenetic protein 2 in colorectal cancer cells with the expression of protein 2, thereby leading to differentiation and reduced proliferation of colorectal cancer cells (Kodach et al, 2011).…”
Section: Fig 2 Evaluation Of Pi3k and Mapk Pathways In Tsc2mentioning
confidence: 99%